Building Breakthrough Products Using AI Research - Ghotbi, Nick; White, Ryen W. (2018)
Artificial intelligence (AI) plays an increasingly important role in our lives. More and more of the applications and services we use each day are enhanced by AI technology. One example is Portrait Mode on the Apple iPhone, where AI is used to intelligently blur photo backgrounds in real time. Integrating AI research outcomes into products is a challenging endeavor that requires close collaboration between research and engineering teams. We address the challenge of taking existing breakthrough research—sourced internally within an organization, or externally, e.g. in academia—in a new area where there is clear market opportunity for building a product around it. We ground this with examples of the work our team did on imbuing Cortana, Microsoft’s digital assistant, with new AI capabilities centered on identifying “commitments” (promises) made in outgoing emails. We offer the lessons learned on our journey and the steps you can take to ship products and services augmented by groundbreaking AI research.